HUBUNGAN KECEMASAN DAN MOTIVASI DENGAN KONSENTRASI BELAJAR MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SURAKARTA - Syaifudin Zuhri (Jurnal Cakrawala Ilmiah, 2025)
Concentration in learning is a crucial determinant of academic success, particularly for medical students who navigate a demanding and intricate educational journey. The intention of this research aimed to investigate the relationship among the anxiety and the motivation on learning concentration of students of the Faculty of Medicine, Universitas Muhammadiyah Surakarta. An analytical pragmatic design with a cross-sectional method was employed. This study’s population encompassed all the students of the Faculty of Medicine, Universitas Muhammadiyah Surakarta, who met the inclusion criteria. A purposive sampling technique was utilized to select 94 students from the 2021 cohort. Data collection instruments included a learning concentration questionnaire, HARS (Hamilton Anxiety Rating Scale) and the MSLQ (Motivated Strategies for Learning Questionnaire). Data analysis involved univariate analysis, the bivariate analysis used Fisher's Exact Test and multivariate analysis used logistic regression. The founding of this study are: A possitive association between anxiety and student learning concentration (p-value=0.000, P < 0.05), A positive association between motivation and student learning concentration (p-value = 0.000, p < 0.05) and A positive multivariate relationship between anxiety and motivation on student learning concentration. In conclusion, this study demonstrates a positive relationship betwixt anxiety and motivation on the concentration of medical students’ learning behavior at the Faculty of Medicine in Universitas Muhammadiyah Surakarta.